2012
DOI: 10.1039/c2cp40493a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of LiAlH4–THF formation by direct hydrogenation of catalyzed Al and LiH

Abstract: The formation of LiAlH(4)-THF by direct hydrogenation of Al and LiH in tetrahydrofuran (THF) was investigated using spectroscopic and computational methods. The molecular structures and free energies of the various possible adducts (THF-AlH(3), THF-LiH and THF-LiAlH(4)) present in a LiAlH(4)/THF solution were calculated and the dominant species were determined to be contact ion pairs where three THF molecules coordinate the lithium. Raman and X-ray absorption spectroscopy were used to investigate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Among numerous possible hydrogen storage materials, lithium aluminum hydride [7][8][9][10] (LiAlH 4 ) is a promising candidate due to its relatively large theoretical hydrogen storage capacity and high potential reversible hydrogenation capability.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…Among numerous possible hydrogen storage materials, lithium aluminum hydride [7][8][9][10] (LiAlH 4 ) is a promising candidate due to its relatively large theoretical hydrogen storage capacity and high potential reversible hydrogenation capability.…”
Section: -6mentioning
confidence: 99%
“…The X-ray intensity was tested over the 2q angle ranged from 10 to 90 with a scanning velocity of 0.02 per second. (Fig.…”
mentioning
confidence: 99%
“…Hydrogen holds enormous potential to be the ultimate energy carrier of the future [1][2][3][4][5]. Yet the lack of an effective method for storing hydrogen with high density currently restrains its widespread utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the reversibility of this step is generally believed to be thermodynamically impossible under practical conditions of temperature and pressure [3,4]. Indeed, theoretical studies have suggested the need for extreme hydrogen pressures >100 MPa at room temperature for the direct regeneration of LiAlH 4 from Li 3 AlH 6 [2,3,5]. In Step 2, Li 3 AlH 6 decomposes via an endothermic reaction with a ∆H of 25 kJ·mol −1 H 2 [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation